Programmed death ligand 1 expression in hepatocellular carcinoma: Relationship With clinical and pathological features. Issue 6 (9th August 2016) - Calderaro, Julien; Rousseau, Benoît; Amaddeo, Giuliana; Mercey, Marion; Charpy, Cécile; Costentin, Charlotte; Luciani, Alain; Zafrani, Elie‐Serge; Laurent, Alexis; Azoulay, Daniel; Lafdil, Fouad; Pawlotsky, Jean‐Michel
Abstract : The prognosis of hepatocellular carcinoma (HCC) remains poor, with only one third of patients eligible for curative treatments and very limited survival benefits with the use of sorafenib, the current standard of care for advanced disease. Recently, agents targeting the programmed death ligand 1 (PD‐L1)/programmed death receptor 1 (PD‐1) immune checkpoint were shown to display impressive antitumor activity in various solid or hematological malignancies, including HCC. PD‐L1 immunohistochemical expression is thought to represent a biomarker predictive of drug sensitivity. Here, we investigated PD‐L1 expression in a series of 217 HCCs and correlated our results with clinical and histological features and immunohistochemical markers (PD‐1, cytokeratin 19, glutamine synthetase, and β‐catenin expression). PD‐L1 expression by neoplastic cells was significantly associated with common markers of tumor aggressiveness (high serum alpha‐fetoprotein levels, P = 0.038; satellite nodules, P < 0.001; macrovascular invasion, P < 0.001; microvascular invasion, P < 0.001; poor differentiation, P < 0.001) and with the progenitor subtype of HCC (cytokeratin 19 expression, P = 0.031). High PD‐L1 expression by inflammatory cells from the tumor microenvironment also correlated with high serum alpha‐fetoprotein levels ( P < 0.001), macrovascular invasion ( P = 0.001), poor differentiation ( P = 0.001), high PD‐1 expression ( P < 0.001), and the so‐called lymphoepithelioma‐like histological subtype of HCC ( P = 0.003). Conclusion : PD‐L1 expression by either neoplastic or intratumoral inflammatory cells is related to tumor aggressiveness and suggests that the response to treatments targeting the PD‐L1/PD‐1 immune checkpoint could be restricted to particular HCC variants; thus, enrichment of these tumor subtypes in future clinical trials should be considered. (Hepatology 2016;64:2038‐2046)